A Comprehensive Examination of UV-VIS Spectrophotometric Methods in Pharmaceutical Analysis Between 2015-2023 - Daştan, Kerem; Eneş, Duygu; Kaplan, Ozan; Dogan, Aysegul; Çelebier, Mustafa (Combinatorial Chemistry & High Throughput Screening, 2025)
Background Quality control is a system of validated procedures in which many samples, including active pharmaceutical ingredients and final products, are analyzed using standard or validated analytical methods. Methods Analytical methods used in analyzing active pharmaceutical ingredients or final products in the pharmaceutical industry can be methods registered in pharmacopeias and developed by the company itself. For this reason, published papers related to pharmaceutical analysis attract analysts and researchers' attention. In this study, pharmaceutical analysis and bioanalysis studies carried out between 2015 and 2023 were examined using Google Scholar, and the recent trends were determined for pharmaceutical analysis. Among the published papers performing conventional analytical techniques for pharmaceutical analysis, those applying UV-VIS spectrophotometry method were selected to predict a future perspective in this study. In addition to the data obtained, the current situation of the pharmaceutical industry was considered to correlate with the obtained data for pharmaceutical analysis. Results The results were presented with comparative tables and summarizing graphs. Interpreting the results allowed us to determine the trends that pharmaceutical analysis studies will lead in the future. This study can be helpful for researchers working on pharmaceutical analysis in both the industry and academia to predict future trends in pharmaceutical analysis. As a result of the literature research covering the dates 2015-2023, 56% of UV-VIS Spectrophotometric methods are used on pharmaceutical dosage forms, 27% are bulk, 16% are pure, 2% are biological materials, and 0.4% are herbal made from materials. Of these studies, 28% were conducted in the 200-240 nm range, 27% were conducted in the 240-300 nm range, and only 44% were conducted at >300 nm. Interpreting the results allowed us to determine the trends that pharmaceutical analysis studies will lead in the future. Conclusion This study can be helpful for researchers working on pharmaceutical analysis in both the industry and academy side to predict future trends for pharmaceutical analysis.
Keywords: google scholar